STRUCTURAL SYSTEM RELIABILITY AND THERMAL CONDITIONS OF COMMUNITY-BUILT CONCRETE DOME MOSQUE BUILDINGS IN DEMAK REGENCY - Kusyanto, Mohhamad
Community-based mosque construction is common in Indonesia, so the technical reliability of such buildings must be assessed because of risks to safety, comfort, health, and convenience affecting many people. These concerns about risk are particularly relevant in Indonesia, where many experience earthquakes and must cope with the tropical heat during the day. The number of reports of building damage due to structural system failures after earthquakes and the use of fans and air conditioners in self-supporting concrete dome mosques affects building reliability in terms of safety and comfort, which is very relevant for further studies. This study aims to describe structural system characteristics and thermal conditions of community-built concrete domed mosques; estimate safety risks in terms of structural system reliability and thermal conditions of mosques; and formulate community self-help development strategies based on mosque domes. The concrete domed mosque is designed for the community because it symbolizes Islamic architecture. The mosque is designed using building materials such as stone for the roof and bricks for the building envelope, with the aim of improving building system quality and the condition of the mosque. In addition, the limited ability of the community with respect to financial and knowledge aspects of development is an important research aspect in the study of the technical performance of concrete domed mosques in Demak Regency. Data collection was conducted through surveys to determine mosques from which data could be retrieved. Physical data of buildings were collected by measuring dimensions and shapes and identifying materials, followed by creating depictions of the mosque buildings. Thermal performance data were collected using wet and dry thermometers, a globe thermometer, an infrared thermometer, and an anemometer to obtain an effective temperature comfort index (ET), while building process data were collected using a questionnaire with development committee respondents, including community leaders, clerics, and elders. Analysis of the distribution, correspondence, comparison, and clusters of the mosque design data were vaulted for thermal conditions and structural systems. To confirm the 4 reliability of the structural system, a digital simulation of frame structure deformation was added with ETABS version 9.6. The risks associated with community-built concrete domed mosques are: 1) large concrete dome spans with dome-retaining structures supported by cantilevered beams and secondary columns very much at risk of cracking or breaking, causing the concrete dome to collapse; 2) a lack of open area, or Window to Wall Ratio (WWR), which impedes the thermal comfort of its users; 3) the distance between buildings, which blocks the flow of air into the space; and 4) concrete roofs and brick walls act as thermal masses, which store and release heat into the environment, affect the reliability of concrete domed mosque buildings in terms of safety and thermal conditions. Building reliability risks can be reduced through strategies that include: 1) designing building structures that support dome structures directly with columns, based on building structure rules; 2) designing cantilever structures with diagonal elements (bracing); 3) using lightweight structures for domes and roofs; 4) designing ventilation openings using digital simulations; and 5) reducing the effect of thermal masses by adding sunlight exposure based on vegetation and thermal insulation. This research concludes that: 1) the community does not yet have the ability to apply the rules of earthquake-resistant structural systems to concrete domed mosques; 2) the community does not understand the environmental conditions of the tropical region and their influence on mosque design, impacting the thermal quality of the mosque space; 3) the community has not been able to adapt mosque architectural form and style to the seismic conditions and tropical environment, 4) the community, which is in the process of self-help development, needs assistance with technical aspects of the building structure and knowledge of thermal environment design; and 5) community-based development is influenced by the characteristics of the community; therefore, technical assistance must be adjusted to such characteristics